BSCI-18. ABLATION OF Csf2 MITIGATES RADIATION-INDUCED NEUROCOGNITIVE DECLINE INDEPENDENT OF HIPPOCAMPAL NEUROGENESIS. (12th August 2019) - Gokhan, Sölen; Aronson, Kyle; Altun, Yagiz; Chitu, Violeta; Brodin, N Patrik; Stanley, E Richard; Mehler, Mark; Tomé, Wolfgang
Abstract: PURPOSE: The results of the RTOG 0933 and NRG CC001 clinical trials have shown that physical sparing of the hippocampus during cranial irradiation (CI) is associated with preservation of memory functions at 4- and 6-months following therapy. Whereas the putative roles of protection of neural stem cells (NSCs) residing within the subgranular zone (SGZ) of the dentate gyrus are presently poorly defined, suppression of inflammation may be involved because ablation of microglia (MG) through blockade of the CSF-1R or selective targeting of CCR2 + macrophages using an appropriate CCR2 inhibitor leads to the retention of hippocampal-dependent cognitive abilities following CI. Inhibition of Colony stimulating factor 2 (CSF-2), a proinflammatory cytokine causing the proliferation and activation of microglia, may be a suitable alternative strategy to alleviate inflammation. METHODS: Our studies have evaluated the effects of ablation of Csf2 and also the inducible ablation of MG on the properties of neuroinflammation, neurogenesis and CI-associated cognitive impairments employing the requisite mouse models. RESULTS: We demonstrate that preservation of cognitive functions following CI does not require ablation of MG. In addition, the reduction in neuroinflammation following Csf2 ablation was sufficient to prevent CI-induced cognitive decline. Moreover, Csf2 ablation did not prevent the deficit in neurogenesis, thereby suggesting that NSC-mediated SGZ neurogenesis is not required for the prevention of radiation-induced cognitive dysfunction. CONCLUSION: We have previously shown that MG play seminal roles in neural development and adult homeostasis and plasticity. Our present study demonstrates that selective modulation of MG-associated neuroinflammatory signaling without MG ablation is a novel therapeutic strategy to preserve cognitive functions following CI. These experimental observations have seminal implications for patients undergoing radiation therapy for tumors of the brain or head and neck in which the hippocampus inevitably exposed to a high dose of radiation leading to potentially debilitating and possibly avoidable cognitive deficits.